Assimilating Spiritual Intelligence into Women’s Academic Leadership Practices in Malaysian Higher Educational Institutions (Journal of Asian Development Studies, 2020)
Spiritual intelligence has been portrayed as an important contributor to an enhanced sense of meaning and purpose within workplace leadership. Despite a growing body of literature significant gaps remain, particularly in understanding how spiritual intelligence is experienced and practiced by women leaders from non-Western countries. To address this gap, we set out to better understand how women academic leaders integrate spiritual intelligence practices within higher education environments. Phenomenological inquiry was used as a method of study. The findings generated two main approaches of integrating and assimilating spiritual intelligence into leadership practice: 1) To work with purpose and meaning; and 2) fostering and demonstrating shared values. We conclude that spiritual intelligence can serve as a way to transform the workplace into being more meaningful and purposeful by creating ‘spiritual’ -- i.e. balanced and harmonious -- relationships between and within employees.